Physical and Structural Characterization of Underutilized Climate-Resilient Seed Grains: Millets, Sorghum, and Amaranth - Geisen, Sarah; Krishnaswamy, Kiruba; Myers, Rob (Frontiers in Sustainable Food Systems, 2021)
While the world is facing food and nutritional challenges leading to the multifaceted burden of malnutrition (underweight and overweight), there is a need to sustainably diversify and explore underutilized crops. Climate-resilient crops, which have the potential to withstand climate crises, have drought resistance, and provide healthy foods with essential vitamins and minerals. Ancient seed grains like amaranth, millets, and sorghum are highly nutritious seed grains that are underutilized, and there is a need for comprehensive research into their properties. This study will specifically investigate amaranth alongside barnyard, finger, kodo, little, pearl, proso millets, and sorghum. Physical and structural properties of the ancient seed grains can provide useful data for storage and food processing. The angle of repose, porosity, and water activity of the grains varied from 19.3° to 23.9°, 3.6 to 17.4%, and 0.533 to 0.660 at 25.5°C, respectively. Additionally, Scanning Electron Microscopy (SEM) was used to observe the surface characteristics and overall shape of each grain. SEM images of the millets shows the impact of dehulling on the surface morphology of the grains (little, barnyard, proso, and kodo millets). This calls for research and development of novel food processing technologies to minimize loss and damage during processing of climate-resilient crops.